Design and implementation of the MMC simulation system in the heterogeneous FPGA‐CPU platform. Issue 16 (13th February 2019) - Li, Xiongfei; Mu, Qing; Zhang, Xing; Xiang, Yinxing; Li, Qiao; He, Guanghui
Abstract : Real‐time simulation of a modular multilevel converter (MMC) plays an important role on the area of large‐scale power electronics research. The authors propose a real‐time MMC simulation system in a heterogeneous computing platform containing the central processing unit (CPU) and field programmable gate array (FPGA). This system decouples the MMC circuits from the grid based on the alternative circuit equivalent model of the MMC bridge arm. Furthermore, the parallel calculation of the equivalent circuits is achieved when the peripheral circuit is realised on the CPU and the MMC arms are realised on FPGA. In addition, a timing optimisation strategy is discussed to reach the timing target requirement. To validate the MMC simulation system, a case study of a grid with 12 MMC bridges and 640 sub‐modules per bridge at 2 μs time step on Xilinx Virtex‐7 XC7VX690T FPGA is simulated in real time. The real‐time simulation results demonstrate high accuracy of the simulation system in comparison to the offline simulation of the original system in the electromagnetic transient program and our design is competitive to recent published works.